The basal ganglia select the expected sensory input used for predictive coding - Colder, Brian (Frontiers in Computational Neuroscience, 2015)
While considerable evidence supports the notion that lower-level interpretation of incoming sensory information is guided by top-down sensory expectations, less is known about the source of the sensory expectations or the mechanisms by which they are spread. Predictive coding theory proposes that sensory expectations flow down from higher-level association areas to lower-level sensory cortex, and deviations from those expectations (error signals) flow back up to association areas. A separate theory of the role of prediction in cognition describes "emulations" as linked representations of potential actions and their associated expected sensation that are hypothesized to play an important role in many aspects of cognition. The expected sensations in active emulations are proposed to be the top-down expectation used in predictive coding. Representations of the potential action and expected sensation in emulations are thought to be instantiated in distributed cortical networks. Combining predictive coding with emulations thus provides a theoretical link between the top-down expectations that guide sensory expectations and the cortical networks representing potential actions. Now moving to theories of action selection, the basal ganglia has long been proposed to select between potential actions by reducing inhibition to the cortical network instantiating the desired action plan. Integration of these isolated theories